Durable Goods and Poverty Measurement - Amendola, Nicola; Vecchi, Giovanni (World Bank Group, Washington, DC, 2014)
The paper focuses on durable goods and their role in the measurement of living standards. The paper reviews the theoretical underpinnings of the methods available to estimate the value of the services flowing from consumer durable goods. It also provides a unified framework that encompasses the acquisition approach, the rental equivalent approach, and the user cost approach. The pros and cons of each method are discussed in the context of poverty and inequality analysis and it is argued that the user cost should receive the highest consideration.